High Ultrafiltration Increasing Intradialytic Blood Pressure on Hemodialysis Patients - Armiyati, Yunie; Hadisaputro, Suharyo; Chasani, Shofa; Sujianto, Untung (University of Muhammadiyah Semarang, 2021)
The increase in blood pressure when the patient is undergoing hemodialysis is experienced by patients with intradialytic hypertension. This condition can be very dangerous for the patient, must be prevented and needs to be controlled. Prevention can be done by controlling variables that can affect intradialytic blood pressure, including ultrafiltration during hemodialysis. This study aims to analyze the relationship between ultrafiltration (ultrafiltration goal, ultrafiltration rate) and intradialytic blood pressure. This research was a descriptive-analytic study with a cross-sectional design, with 112 samples at two centres of dialysis in Semarang. Data were analyzed using the Spearman Rho. The finding obtained showed that ultrafiltration goal (UFG) and ultrafiltration rate (UFR) correlated with intradialytic blood pressure (systolic, diastolic and mean arterial pressure). The magnitude of UFG an associated with increase in intradialytic systolic (p=0,024; r=0,213), increase in intradialytic diastolic (p=0,007; r=0,252) and increase in mean arterial pressure (p=0,016; r=0,227). High UFR is associated with with increase in intradialytic systolic (p=0,037; r=0,211), increase in intradialytic diastolic (p=0,001; r=0,320) and increase in mean arterial pressure (p=0,034; r=0,200). Determination of ultrafiltration during hemodialysis must be done carefully and precisely to prevent an increase in intradialytic blood pressure.